Potato production, marketing, and utilization in Meghalaya, India: Results of a value chain assessment. - Chulet, H.; Anantharaman, M.; Shanpru, E.; Prain, Gordon (International Potato Center, 2017)
Potato is a vital and inseparable part of livelihoods and diets in Meghalaya and improvements in its value chain can benefit the entire sector, particularly smallholder potato farmers. Value chain mapping in three districts in Meghalaya revealed that farmers, traders, wholesalers, retailers, and consumers are the main value chain factors, supported by input suppliers and government organizations. The potato value chain can be strengthened by enhancing potato producers’ access to inputs, better post-harvest handling, quality control mechanisms, and the use of proper storage. Potential interventions in potato marketing include providing market intelligence, building the entrepreneurial capacity of farmers, identifying processing options, and developing a branding strategy for Meghalaya potatoes to market to other states.